2009
DOI: 10.1007/s00442-009-1374-1
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm and belowground competition effects on plant productivity in a plant diversity gradient

Abstract: Diversity is one major factor driving plant productivity in temperate grasslands. Although decomposers like earthworms are known to aVect plant productivity, interacting eVects of plant diversity and earthworms on plant productivity have been neglected in Weld studies. We investigated in the Weld the eVects of earthworms on plant productivity, their interaction with plant species and functional group richness, and their eVects on belowground plant competition. In the framework of the Jena Experiment we determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 44 publications
2
60
0
1
Order By: Relevance
“…In a grassland biodiversity experiment, Marquard et al (2009b) found that increased density of overyielding species in mixtures to be the main driver of the positive biodiversity-productivity relationship-a mechanism that may be driven in part by earthworms. In the same experiment, earthworms enhanced plant community productivity (Eisenhauer et al 2009b). However, experimental evidence for the significance of belowground ecosystem engineers in grassland biodiversity experiments is scarce, coming solely from the investigation of earthworm effects in the Jena Experiment.…”
Section: Ecosystem Engineersmentioning
confidence: 92%
See 1 more Smart Citation
“…In a grassland biodiversity experiment, Marquard et al (2009b) found that increased density of overyielding species in mixtures to be the main driver of the positive biodiversity-productivity relationship-a mechanism that may be driven in part by earthworms. In the same experiment, earthworms enhanced plant community productivity (Eisenhauer et al 2009b). However, experimental evidence for the significance of belowground ecosystem engineers in grassland biodiversity experiments is scarce, coming solely from the investigation of earthworm effects in the Jena Experiment.…”
Section: Ecosystem Engineersmentioning
confidence: 92%
“…Eisenhauer et al (2009b) concluded that legumes and earthworms benefit from each other's presence and form a loose mutualistic relationship. N-rich legume litter and rhizodeposits beneficially affect earthworm biomass (Milcu et al 2006a, Eisenhauer et al 2009a, while legumes benefit from the presence of earthworms through increased decomposition of plant residues and the associated increase in soil N availability (Eisenhauer and Scheu 2008a).…”
Section: Decomposersmentioning
confidence: 98%
“…Many studies investigated the interactions of earthworms with soil physical conditions, with plants, with soil microorganisms and with other soil invertebrates. These studies demonstrated that earthworms impact the soil physical properties and structure, cause changes in nutrient availability and soil respiration, affect the biomass and composition of soil microorganisms, density of other soil invertebrates, composition of plant communities and aboveground food webs mainly due to their activities (Abbott and Parker 1981;Martin 1982;Doube et al 1994;Bohlen and Edwards 1995;Fraser et al 2003;Wurst et al 2003;Eisenhauer et al 2007Eisenhauer et al , 2009Eisenhauer et al , 2010Boyer et al 2013;Doan et al 2013;etc.). The burrowing activities of earthworms cause changes in the soil structure and earthworms have important function in soil formation-they consume organic matter, fragment it, mix it with soil mineral particles and form water-stable aggregates (Edwards 2004).…”
Section: Role Of Earthworms In Soil Ecosystemsmentioning
confidence: 98%
“…This is in agreement with the findings of Cameron et al (2012), showing that EM colonization of white spruce roots remains unaffected by the presence of EWs. Likewise, other studies found no effect of EWs on AM root colonization (Eisenhauer et al, 2009;Wurst and Rillig, 2011).…”
Section: Earthworms Do Not Affect Mycorrhizal Colonization But Modifymentioning
confidence: 98%
“…However, in the literature, contrasting evidences are reported. For example, in a field experiment, the amount of N mobilized from straw litter and taken up by maize plants increased in the presence of both EWs and AM fungi (Li et al, 2013), while in experiments using grass litter, the effect of EWs on plant N uptake in the presence or absence of AM was not significant (Wurst et al, 2004;Eisenhauer et al, 2009). The extent to which the impact of interaction between EWs and mycorrhizal fungi on N nutrition depends on habitat conditions, such as soil and litter quality (Milcu et al, 2008;Holdsworth et al, 2012) is unknown.…”
Section: Introductionmentioning
confidence: 94%